Nutritional Value of Cassa occidentalis and its Potential Contribution to Aquaculture Feed - Oshoke, J.O.; Akinyemi, A.O. (Pakistan Journal of Nutrition, 2015)
This study was carried out to assess the nutrient composition of Cassa occidentalis as a protein supplement source in the diets of fish to enhance their productivity. Proximate composition results showed high dry matter (95.65%), crude fiber (11.92%), nitrogen free extract (61.88%) and calorific value (1483.26 kcal/100 g), but low ether extract (3.69%) and crude protein (18.74%). The amino acid profile reveals a high concentration of leucine (6.23 g/100 g protein), histidine (2.27 g/100 g protein), proline (3.36 g/100 g protein) and glycine (3.51 g/100 g protein), Arginine (4.83 g/100 g protein) while the rest of the amino acids were low concentration in the raw seed. The concentration of anti-nutrients in the legume seeds recorded low values (0.99 and 0.14% and 0.28 mg/100 g) for Phytic acid, tannin and phytate respectively, while oxalate and cyanogenic glycoside levels were high. C. occidentalis seed is a good source of amino acid but it contained some antinutritional factors that must be deactivated for effective utilization in fish feed and also processing of the seeds will definitely improve the crude protein content.